-(8y+4)-(-7y-7)=-1

Simple and best practice solution for -(8y+4)-(-7y-7)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(8y+4)-(-7y-7)=-1 equation:


Simplifying
-1(8y + 4) + -1(-7y + -7) = -1

Reorder the terms:
-1(4 + 8y) + -1(-7y + -7) = -1
(4 * -1 + 8y * -1) + -1(-7y + -7) = -1
(-4 + -8y) + -1(-7y + -7) = -1

Reorder the terms:
-4 + -8y + -1(-7 + -7y) = -1
-4 + -8y + (-7 * -1 + -7y * -1) = -1
-4 + -8y + (7 + 7y) = -1

Reorder the terms:
-4 + 7 + -8y + 7y = -1

Combine like terms: -4 + 7 = 3
3 + -8y + 7y = -1

Combine like terms: -8y + 7y = -1y
3 + -1y = -1

Solving
3 + -1y = -1

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -1y = -1 + -3

Combine like terms: 3 + -3 = 0
0 + -1y = -1 + -3
-1y = -1 + -3

Combine like terms: -1 + -3 = -4
-1y = -4

Divide each side by '-1'.
y = 4

Simplifying
y = 4

See similar equations:

| (2y-x+3z-13)-(4x+2-5y)+(6z+8)= | | 2.3-7x=-25.7 | | s^2=1+s(1-3s) | | (2bx+9x+4a)-(4bx-a)+(3b+a)= | | 6(3x-5)=3(6x+6) | | -2(q-4)=3q+12 | | 8(3a+7c)-6(2a+6c)= | | (2a^2b+7ab^2)+(3ab^2-2a^2b)= | | 8+2s-7=7s+3-4s | | -(3y+1)-(-2y-4)=-1 | | 3(x-2)(x+1)=0 | | -2y+6=20 | | 4z-7=5(5z-3) | | (5b-1)(6b-3)= | | 2x+20=304 | | -6x-(9y+(5x-(-2y-b))-(2b+a))= | | 2t^2-20t=0 | | 2(3v-1)+7v+7=5(v-6)+3v | | 304=s+20 | | 304=s+20w | | (4+w)(5w-8)=0 | | 30+9y=16y | | 5(w+2)-6(w+4)=0 | | (-6x-z)-(3y+(7x-(3z+8y+x)))= | | (5w+6)(5w-6)= | | -X+2x^2=0 | | -(8y+2)-(-7y-5)=-1 | | B=b+2a+3c | | 8(3x-8)=2(12x+7) | | (18y^2-12xy)-(6y^2+xy-a)= | | 3+3s-2=8s+5-3s | | 4(3w+1)+4v=4(v-6)-2v |

Equations solver categories